Identification of heterogeneous constitutive model of laser additive manufactured materials based on nano-indentation test and orthogonal metal cutting - Meng Liu; Guohe Li; Shanshan Zhao; Feng Wang; Lei Li; Yujun Cai; Chunzheng Duan (Journal of Materials Research and Technology)
The microstructure and micro-hardness distribution of laser additive-manufactured (AM-ed) materials exhibit significant heterogeneity, making it difficult to obtain accurate dynamic plastic constitutive models. This paper proposes a novel approach to derive a heterogeneous constitutive model for the laser AM-ed materials, utilizing nano-indentation tests and orthogonal cutting experiments. Nano-indentation tests were conducted to obtain indentation load-depth curves for various zones within laser AM-ed alloys. Through the energy method and finite element inversion analysis, heterogeneous power-law constitutive models were established. Additionally, orthogonal cutting experiments, combined with Oxley's model, were employed to calculate key parameters such as equivalent shear strain, shear strain rate, shear stress, and temperature in the primary deformation zone. These parameters, when integrated with the power-law models, facilitated the development of Johnson-Cook constitutive models specifically tailored for the AM-ed materials. The findings demonstrate that these constitutive model accurately capture the heterogeneous nature of AM-ed materials and effectively characterizes their dynamic mechanical behavior under conditions of large strain (up to 5), high strain rate (up to 105 s−1), and high temperature (up to 850 °C). Furthermore, finite element simulations of cutting force and chip morphology in different zones of AM-ed materials exhibits excellent agreement with experimental results. The maximum prediction errors for main cutting force and feeding force are 10.87% and 12.71%, highlighting the precision of the developed Johnson-Cook constitutive model. In addition, the heterogeneous characteristics have a significant impact on the machinability, and the research results can provide help for machining mechanism and process optimization of laser AM-ed materials.